Velamentous Insertion of Umbilical Cord: A Case Report and Review of the Literature - Ayşe Uysal Derbent; Neval Çayönü; Mustafa Sakallı; Mehmet Karaca; Selahattin Kumru (Medical Network, 2012)
Velamentous cord insertion (VCI) is an abnormal cord insertion in which the umbilical vessels coursing through the fetal membranes before inserting into the placental disk. VCI is associated with fetal growth restriction, preterm labor, abnormal intrapartum fetal heart rate (FHR) pattern, abruption of the placenta, and neonatal death. Prenatal detection of umbilical cord abnormalities may reduce perinatal morbidity and mortality. In this study, we reviewed the literature over a case with VCI.